A practical guide to prescribing sublingual immunotherapy tablets in North America for pediatric allergic rhinoconjunctivitis: an injection-free allergy immunotherapy option - Blaiss, Michael; DuBuske, Lawrence; Nolte, Hendrik; Opstrup, Morten; Rance, Karen (Frontiers in Pediatrics, 2023)
Allergic rhinoconjunctivitis (ARC) is a common disease that affects individuals of all ages. Pediatricians may be the first (and only) point of care for children with ARC. Sublingual immunotherapy (SLIT)-tablets are a convenient at-home, injection-free allergy immunotherapy option that can be used for the treatment of ARC. This paper provides a practical guide for pediatricians to aid in prescribing SLIT-tablets to children with ARC in North America. Topics include a summary of the available SLIT-tablets and their efficacy and safety, guidance on when SLIT-tablets are an appropriate option, and how to diagnose ARC and identify culprit allergens. Practical guidance is also provided through a proposed decision tree, a prescribing checklist and prescribing procedures, and suggested follow-up assessments.